2022
DOI: 10.3389/fphy.2022.868339
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Director State in Gadolinium Gallate Garnet

Abstract: In recent years the topic of frustrated magnetism has attracted significant scientific interest that shows little sign of abating. Within the field of frustrated magnetism, the compound Gd3Ga5O12 was, for many years, the archetypal frustrated magnet with a ground state that could not be elucidated. Recently an unusual emergent ground state, a director state, has been determined for Gd3Ga5O12, which is now also observed for other isostructural compounds. In this review an overview of the director state is given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The magnetic Mn ions are positioned on the A site, forming two interpenetrating hyperkagomé lattices in which the magnetic ions are arranged in corner sharing triangles. These adjacent triangles lie with an angle of 73.2 • between them, creating a three dimensional structure [4]. The antiferromagnetically coupled ions on the triangular lattice facilitate geometric magnetic frustration, prompting interest in the garnet structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnetic Mn ions are positioned on the A site, forming two interpenetrating hyperkagomé lattices in which the magnetic ions are arranged in corner sharing triangles. These adjacent triangles lie with an angle of 73.2 • between them, creating a three dimensional structure [4]. The antiferromagnetically coupled ions on the triangular lattice facilitate geometric magnetic frustration, prompting interest in the garnet structure.…”
Section: Introductionmentioning
confidence: 99%
“…The gadolinium gallium garnet (GGG), Gd 3 Ga 5 O 12 , has been extensively studied as the archetypal frustrated magnet [4,[15][16][17]. GGG displays no long-range magnetic order in zero-field despite its relatively strong antiferromagnetic correlations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, Yb 3 Ga 5 O 12 , which is predicted to have excellent phase stability by Song et al, was therefore selected to identify the possible oxide ion conduction. While gallium-based garnet materials have been extensively studied for their magnetic and photoluminescence properties , and applications in solid-state lasers, there is a scarcity of research on their electrical properties. In the present work, for the first time, we reported that Ca doping to create oxygen vacancies could successfully introduce oxide ion conduction and significantly improve the electrical conductivity of Yb 3 Ga 5 O 12 by more than two orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%